Coconut Residue-Derived Nanoporous Carbon via Hydrothermal Carbonization for Nanoporous Carbon-Based Supercapacitor Electrodes - Ruenroengrit, Kemchat; Kunyuan, Jumpon; Ruttanadech, Nuttapong; Kaewtrakulchai, Napat; Puengjinda, Pramote; Chaiammart, Nattapat; Chutipaijit, Sutee; Buasri, Achanai; Fuji, Masayoshi; Eiad-Ua, Apiluck; Panomsuwan, Gasidit (My University, 2025)
The increasing demand for sustainable and cost-effective energy storage solutions has driven interest in biomass-derived carbon materials for supercapacitor electrodes. This study explores the valorization of coconut residue (CR), an abundant agricultural waste, as a carbon precursor for nanoporous carbon (NPC) production. NPC was synthesized via hydrothermal carbonization (HTC) of CR, followed by chemical activation using potassium hydroxide (KOH) at varying temperatures (700, 800, and 900 °C). The effects of activation temperature on the structure and electrochemical performance of the NPC were systematically investigated. The activated materials exhibited amorphous, highly porous structures, with surface areas increasing alongside activation temperature—reaching a maximum of 1969 m2 g−1 at 900 °C. Electrochemical characterization was conducted using a three-electrode setup through cyclic voltammetry (CV) and galvanostatic charge–discharge (GCD) in a 1 M Na2SO4 electrolyte. The sample activated at 900 °C with a CR:KOH weight ratio of 1:2.5 achieved the highest specific capacitance of 52 F g−1 at a specific current of 1 A g−1. These findings underscore the potential of CR as a low-cost and sustainable raw material for fabricating efficient electrode materials in energy storage applications.
Keywords: coconut residue; hydrothermal carbonization; KOH activation; nanoporous carbon; supercapacitor electrodes